Addressing influenza in Bangladesh: closing evidence and policy gaps with strategic interventions - Md Zakiul Hassan; Saleh Haider; Mohammad Abdul Aleem; Md Ariful Islam; Tanzir Ahmed Shuvo; Saju Bhuiya; Mahbubur Rahman; Mahmudur Rahman; Tahmina Shirin; Fahmida Chowdhury (The Lancet Regional Health - Southeast Asia)
Summary: Since the establishment of the National Influenza Surveillance Program in 2007, Bangladesh has significantly progressed in monitoring influenza through national and international collaboration. However, this collaboration has not been translated into actionable control policies, which coupled with low vaccination coverage, impose a substantial health and economic burden in Bangladesh. Critical gaps remain in understanding the influenza burden among high-risk populations and the barriers influencing their vaccine uptake. These gaps hinder the development of evidence-based strategies for prevention and control, consequently leaving the country vulnerable to a potentially catastrophic influenza epidemic. These challenges require a multifaceted approach, including continuous local data collection on disease burden and vaccine barriers, vaccine cost-effectiveness analyses, and the design of context-specific interventions. Leveraging existing infrastructures offers opportunities to develop tailored strategies for high-risk populations. A robust national influenza policy is imperative to mitigate the burden and reduce future pandemic threats.